KOMUNIKASI INTERPERSONAL KELUARGA SEBAGAI MEDIASI PERLINDUNGAN PEREMPUAN DAN ANAK DARI KEKERASAN - Bedjo Sukarno (Universitas Slamet Riyadi, 2017)
In the social reality, the adults must protect children and respect the rights of children and women,but the incidence is often carried out against violence unexpected even doing the nearest person becausenot have the awareness to protect it. The first source of pornography, for children are collections of parentswhose shape can be movies, magazines, writing to the picture. It was, because parents are not careful instoring pornographic material, the possibility of pornographic material and then spread easily in socialmedia so that a child's access to it conducted amongst users of social media or through the site is no longera god. Healthy family is a family that is communicative, communication is not just anyone, but moredeeply exchanged through mutual listening, understanding, support to meet the needs of family members,as well as forgiveness and pardon. Interpersonal communication within the family is useful for buildinga family concern and sensitivity so that the needs of each family member are met.Key word : Violence against women and children, Social Media, Family Interpersonal Communication.